A GLUCOSE-TRIGGERED SOLUBILIZABLE POLYMER GEL MATRIX FOR AN INSULIN DELIVERY SYSTEM - CHOI, YK; JEONG, SY; KIM, YH (ELSEVIER SCIENCE BV, 1992)
A poly(acrylamidophenylboronic acid-co-acrylamide) (poly(AAPBA-co-AAM)) gel was synthesized using diglucosylhexanediamine (DGHDA) as a crosslinking agent in order to prepare a glucose-responsive insulin delivery system. The system described here is a water-soluble polymer gel matrix whose erosion rate is glucose-dependent. At physiological pH, in the absence of glucose, anionic tetrahedral complexes between boronic acid moieties of the poly(AAPBA-co-AAM) and glucose moieties of DGHDA were maintained and the release rate of entrapped insulin was low. In the presence of glucose, however, the gel matrix was disrupted by replacement of DGHDA with glucose through competitive binding to boronic acid, resulting in the rapid solubilization of the matrix and a significant increase in the release rate of insulin.
Keywords: AFFINITY-CHROMATOGRAPHY; MONOSACCHARIDES; DEPENDENCE; OXIDASE